Answer:
answer is d
Step-by-step explanation:
from question
g(x) = 2(3x) - 4 = 6x - 4
then put x = 1,2,3
so g(x) = 2,8,14
Answer:
I believe the answer is D. Hope this helps
Step-by-step explanation:
Answer: 2x + y
<u>Step-by-step explanation:</u>
logₐ(3) = x
logₐ(5) = y
logₐ(45) = logₐ(3²· 5)
= logₐ(3)² + logₐ(5)
= 2 logₐ(3) + logₐ(5)
= 2 x + y <em>substituted given values (stated above)</em>
Answer:
4[3x-2]
Step-by-step explanation: 12x-8
Hope this helped out
F(g(x)) = f(x-4) = (x-4)
g(f(x)) = g(x) = x-4